The Rückenfigur: A Note on an Intriguing Rear-View Pictorial Device. (May 2020) - Schott, Geoffrey D.
The Rückenfigur, a rear-view depiction of a person, is an artistic device which dates back several centuries but became particularly prominent in 19th century in Germany. The adoption of the rear-view presents an intriguing challenge, since the viewer must engage with a figure which sees without visible eyes. Considered here are some of the perceptual issues which arise from this unusual pictorial device.